Urban-Rural Interactions Towns as Focus Points in Rural Development - Leeuwen, Eveline; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2010)
Modern Europe has rural roots. Even today, as much as 90 per cent of Europe (EU25) consists of rural areas in which half of the population lives. While different rural areas often face different challenges, the shift from agricultural production towards a multifunctional landscape and the increasing value assigned to environmental values affect all rural areas. The ambition to develop a more diversified rural economy, as well as the bottom-up approach and local focus of many rural policies, require a clear knowledge of the current socio-economic function of towns and town-hinterland linkages. Therefore, the aim of this study is to contribute to the understanding of the current function of towns in Europe in general and in the Netherlands more specifically. By using both micro- and macro-approaches, the multifaceted relationships between town-hinterland and the rural economy are explored at different spatial levels and for different actors, in particular for households, farms and firms.
Town and Hinterland Interactions in Rural Areas -- Multifunctionality of Towns: Exploration of the Spatial Behaviour of Households -- Farms in a Modern World: Local Integration and Off-Farm Employment -- Town-Hinterland Relations: A Social Accounting Matrix Approach -- Microsimulation of Rural Households -- Future Developments in Rural Areas: Combining Micro and Macro -- Conclusions and a Roadmap to Future Research.
Keywords: Economics; Regional planning; Regional economics; Farm economics; Economics/Management Science; Regional/Spatial Science; Landscape/Regional and Urban Planning; Agricultural Economics